Pengaruh berbagai dosis pupuk organik cair urin sapi terhadap pertumbuhan semai durian (Durio zibethinus Murr) di lapangan - Nismawati; Wulandari, Retno; Rahmawati (Jurnal Bisnis Kehutanan dan Lingkungan, 2024)
Cow urine is an alternative to increase the availability, adequacy, and efficiency of nutrient uptake for plants containing microorganisms so that it can reduce the use of inorganic fertilisers (N, P, and K) and increase plant yields to the maximum. The application of liquid organic fertiliser must pay attention to the concentration or dose applied to the plants. This research aims to determine the effect of various concentrations of liquid organic fertiliser made from cow urine on the growth of durian seedlings. This research was carried out for three months, from February to May 2023, at the Arboretum of the Faculty of Forestry, Tadulako University. This research used a completely randomised design (CRD) method consisting of five treatments. M0 = control, M1 = (150 ml POC: 850 ml water), M2 = (200 ml POC: 800 ml water), M3 = (250 ml POC: 750 ml water), and M4 = (300 ml POC: 700 ml water). The five treatments were repeated six times, so the total experimental units were 30. The parameters observed in this research were the increase in seedling height, the increase in the number of seedling leaves, and the increase in seedling diameter. Research data was analysed using analysis of variance. Further tests were carried out using the Honestly Significant Difference (BNJ) test at the 5% level. The results of the variance analysis showed that the application of various concentrations of liquid organic fertiliser made from cow urine had a significant effect on the increase in height, the number of leaves, and the diameter of durian seedlings. Based on the results of the BNJ test at the 5% level, it shows that the average increase in seedling height, number of leaves, and diameter of durian seedlings in the M4 treatment was significantly different from the M3, M2, M1, and M0 treatments. The average increase in height of durian seedlings is M4 = 5 cm, M3 = 4.66 cm, M2 = 4 cm, M1 = 2.91 cm, and M0 = 2.08. Average increase in number of leaves: M4 = 4 pieces, M3 = 3.33 pieces, M2 = 2.66 pieces, M1 = 2.16 cm, and M0 = 1.83. Average increase in diameter: M4 = 1.21, M3 = 1.03, M2 = 0.73, M1 = 0.45, and M0 = 0.28.